2020
DOI: 10.1080/23311975.2020.1772618
|View full text |Cite
|
Sign up to set email alerts
|

National culture as a moderator between social norms, religiosity, and tax evasion: Meta-analysis study

Abstract: The objective of this research is to present the meta-analysis results of the relationship of social norms and religiosity with tax evasion, with national culture as a moderating variable. Previous researches show mixed results of the relationship between social norms, religiosity, and tax evasion. Meta-analysis is considered a way out of saturated and inconsistent research since it provides an efficient and systematic approach to make a robust conclusion. This research synthesizes 54 results of 14 individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 66 publications
0
12
0
1
Order By: Relevance
“…The study of Sutrisno and Dularif (2020) found that national culture plays a pivotal role in moderating the relationship between social norms and tax evasion. However, this was different regarding religiosity and tax evasion.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The study of Sutrisno and Dularif (2020) found that national culture plays a pivotal role in moderating the relationship between social norms and tax evasion. However, this was different regarding religiosity and tax evasion.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Khususnya di Asia, perpajakan telah diterapkan sejak abad ke 17 di Thailand (Constable & Kuasirikun, 2020). Agama Budha selalu mengajarkan umatnya untuk melakukan pengorbanan bukan hanya kepada Tuhan, tetapi juga kepada sesama manusia (Sutrisno & Dularif, 2020). Kejujuran dalam agama Budha berarti tidak berbohong, selalu berbuat baik sesuai dengan hati nuraninya, serta mematuhi peraturan negara dan hukum, termasuk juga tidak menghindari pajak (Huong, 2023).…”
Section: Perspektif Budha Dalam Perpajakanunclassified
“…Cultural indicators differentiate countries on different dimensions (see Bleidorn et al, 2015;Jonason et al, 2020). Previous studies have shown that different dimensions of culture can play moderating roles (e.g., Sutrisno and Dularif, 2020). The socioeconomic context was found to be a moderator in the relationship between depression and body mass index (Alvarez-Galvez and Gomez-Baya, 2017).…”
Section: Country Indicatorsmentioning
confidence: 99%